ANALYSIS OF THE FUNCTIONAL CAPACITY OF INDIVIDUALS WHITH KIDNEY DISEASE IN HEMODYALISIS AT CASCAVEL - PR (Fiep Bulletin - online, 2014)
Chronic kidney disease (CKD ) is considered a public health problem worldwide. In Brazil, the incidence and prevalence of renal failure are increasing , the prognosis is still poor and the cost of treating the disease are very high. The improvement in quality of life of these patients is directly related to the kind of life they lead, feeding and care in physical activity for better health maintenance thereof. Objective: To compare the results obtained in different exercise protocols applied in CRF patients. Methods: The sample consisted of 12 patients with chronic kidney disease undergoing hemodialysis 3 times a week for at least 1 year in the Nephrology Clinic in Cascavel PR . The subjects underwent an interview based on the quality of life questionnaire (SF -36 ), test functional exercise capacity ( shuttle walk test ), and evaluation of the functional autonomy of the group of Latin American development to maturity ( GDLAM ). Conclusion: We concluded that individuals with chronic kidney disease treated at the hemodialysis center in Cascavel - PR, exhibit impairments primarily physical conditions indicating the need for use of physical exercise as an important adjunct in the interdisciplinary treatment of this population.
Keywords: Chronic kidney disease; functional capacity; hemodialysis